Coping strategy for covid-19 in primary health care: experience report in Salvador-BA - Lélia Mendes Sobrinho de Oliveira; Nildete Pereira Gomes; Emanuela Santos Oliveira; Alice de Andrade Santos; Larissa Chaves Pedreira (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective: To report the experience of actions to confront the Coronavirus developed by primary health care in the municipality of Salvador, Bahia, Brazil. Methods: It is an account of the experience carried out by a nurse from the health management of the city of Salvador, in the fight against the Coronavirus, without a period from February 26 to April 26, 2020. Results: A flow of action was elaborated to confront the Coronavirus in the primary health care network, aiming to implement conducts in the face of the pandemic. The professionals were trained to identify suspected cases of contamination and to guide or refer these people to the health service. Conclusion: It was concluded that the construction of a flow to attend suspected cases of contamination by Coronavirus was relevant to mitigate the impacts, protecting the community and professionals involved.